2015
DOI: 10.1159/000430392
|View full text |Cite
|
Sign up to set email alerts
|

Role of Na+-K+-2Cl- Cotransporter 1 in Phenylephrine-Induced Rhythmic Contraction in the Mouse Aorta: Regulation of Na+-K+-2Cl- Cotransporter 1 by Ca2+ Sparks and KCa Channels

Abstract: Background/Aims: Vasoconstrictor-induced rhythmic contraction of arteries or veins has been observed both in vivo and in vitro. Many studies have reported that gap junctions, ryanodine receptors, Na+, K+-ATPase and other factors are involved in vasoconstrictor-induced rhythmic contraction in vascular smooth muscle. However, the mechanism is still not completely understood. Methods: We used vessel tension measurements, intracellular recordings and intracellular Cl- concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(38 reference statements)
3
0
0
Order By: Relevance
“…Instead, bestrophins are required for the rhythmic contractile pattern known as vasomotion (23). This is consistent with the oscillatory Cl Ϫ conductance observed during vasomotion (79), and with the sensitivity of vasomotion to extracellular Cl Ϫ substitution (12) and the NKCC inhibitor bumetanide (142). The effects of Cl Ϫ substitution on arterial tone vary: acute reduction of extracellular [Cl Ϫ ] has been found to potentiate agonist-induced contractions (39-41, 85, 119) and cause VSMC depolarization (111,119), indicating that Cl Ϫ channels are open under the experimental conditions and allow Cl Ϫ efflux down the enhanced electrochemical gradient, whereas long-term exposure to Cl Ϫ -free FIGURE 1.…”
Section: Ca 2؉ -Activated CL ؊ Channelssupporting
confidence: 73%
“…Instead, bestrophins are required for the rhythmic contractile pattern known as vasomotion (23). This is consistent with the oscillatory Cl Ϫ conductance observed during vasomotion (79), and with the sensitivity of vasomotion to extracellular Cl Ϫ substitution (12) and the NKCC inhibitor bumetanide (142). The effects of Cl Ϫ substitution on arterial tone vary: acute reduction of extracellular [Cl Ϫ ] has been found to potentiate agonist-induced contractions (39-41, 85, 119) and cause VSMC depolarization (111,119), indicating that Cl Ϫ channels are open under the experimental conditions and allow Cl Ϫ efflux down the enhanced electrochemical gradient, whereas long-term exposure to Cl Ϫ -free FIGURE 1.…”
Section: Ca 2؉ -Activated CL ؊ Channelssupporting
confidence: 73%
“…Further studies have provred that this is accomplished through the channel opening of NKCC1 which increases the [Cl − ] i above the electrochemical equilibrium which depolarizes the VSMC through activation of voltage-gated Ca 2+ [ 87 ]. Consistent with previous findings, more recent studies in intact isolated thoracic aortas demonstrated that NKCC1 is involved in phenylephrine-induced rhythmic contraction in the mouse aorta and that NKCC1 is regulated by calcium sparks [ 88 ].…”
Section: Role Of Nkcc In Cardiovascular Diseasesupporting
confidence: 88%
“…[78]. Consistent with previous findings, more recent studies in intact isolated thoracic aortas demonstrated that NKCC1 is involved in phenylephrine-induced rhythmic contraction in the mouse aorta and that NKCC1 is regulated by calcium sparks [79].…”
Section: Nkcc In Vascular Cellssupporting
confidence: 84%